Designing of 3-D Animation Videos in Arduino Assembly Learning with The Multimedia Development Life Cycle Method - Sarah Astiti; Krishnanda Raditya Mooduto; Petrus Kerowe Goran; Yunita Ardilla (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2021)
Abstract The interest in the Internet of Things (IoT) field is getting more and more popular in the world of technology this recently. This can be seen from the number of researchers, students and students starting to study the Internet of Things (IoT). If viewed globally, then the notion of the Internet of Things (IoT) is that everything in the form of living or inanimate objects in this universe has a code/identity that can be recognized by a system. Many parties have begun to introduce and teach Internet of Things (IoT) technology to Generation Z children. The thought of the importance of Arduino technology learning media is that it can facilitate the learning process for students and students in recognizing and making Arduino devices. Arduino devices consist of CPU, ROM and RAM. Arduino power supply uses a dc voltage between 9-12 volts. In learning Arduino assembly so far, lecturers do not use supporting media other than direct practice and books and power point slide shows. students also have difficulty in absorbing Arduino assembly subject matter because students are faced with new material that has never been obtained before. In the Internet of Things (IoT) course, there is Arduino assembly material. Arduino assembly material cannot be separated from the practicum. Therefore, students need learning media that can package practical activities into a video that can be studied anywhere and anytime. By using learning video media, it is hoped that there will be an increase in student learning outcomes, especially in Arduino assembly materials. Therefore, in this study, a 3-dimensional animation video will be designed in learning Arduino assembly using the Multimedia Development Life Cycle (MDLC) method.